2021
DOI: 10.1101/2021.05.10.21256939
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Red Blood Cell-Conditioned Media from Non-Alcoholic Fatty Liver Disease Patients Contain Increased MCP1 and Induce TNF-α Release

Abstract: BACKGROUND: Non-Alcoholic Fatty Liver Disease (NAFLD) constitutes a global pandemic. An intricate network among cytokines and lipids possesses a central role in NAFLD pathogenesis. Red blood cells comprise an important source of both cytokines and signaling lipids and have an important role in the molecular crosstalk during immunometabolic deregulation. However, their role in NAFLD has not been investigated in deep. METHODS: Conditioned media from erythrocytes derived from 10 NAFLD patients (4 men, 6 women, ag… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…MCP1 levels in erythrocyte membranes of NASH patients were slightly increased, albeit to marginally non-statistically significant levels. However, increased membrane bound MCP1, in combination to other stimulatory factors, like ATP acting on P2X7 (unpublished results), can promote high MCP1 release from NASH patients’ erythrocytes 14 .…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…MCP1 levels in erythrocyte membranes of NASH patients were slightly increased, albeit to marginally non-statistically significant levels. However, increased membrane bound MCP1, in combination to other stimulatory factors, like ATP acting on P2X7 (unpublished results), can promote high MCP1 release from NASH patients’ erythrocytes 14 .…”
Section: Discussionmentioning
confidence: 89%
“…Interestingly, erythrocyte sphingolipid metabolism can result in the formation of sphingosine 1-phosphate (S1P) 9 , a bioactive lipid mediator, implicated in the pathogenesis of NASH 33 . It has previously been shown that erythrocyte membranes of NASH patients, contain decreased levels of sphingomyelin 34 , and that erythrocyte-conditioned media do not contain elevated S1P 14 . Hence, we wondered, if there is sphingosine accumulation in the erythrocyte membrane in the context of NASH.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations